Design for Assessing the Quality of Internet-Based Governance of Cooperative Legal Entities (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Corporate governance is a crucial factor in preventing corruption while simultaneously enhancing organisational performance and sustainability. In the context of cooperatives as member-based economic entities, implementing good governance continues to encounter various challenges, particularly those related to the limitations of measurement models that are both comprehensive and adaptable to the development of digital technology. This study aims to identify and design a more comprehensive internet-based cooperative governance quality measurement model by employing a qualitative approach through documentation techniques, unstructured interviews, and focus group discussions (FGDs) involving stakeholders such as regulators, cooperative practitioners, and academics. The findings indicate that existing governance measurement models have not yet fully accommodated the complexity of cooperative characteristics and the demands of digitalisation. Consequently, this study develops a new model by integrating five principal aspects, namely stakeholders, transparency, responsibility, accountability, and technical accessibility, which are further elaborated into 167 indicators. The novelty of this research lies in the utilisation of the internet as a governance measurement medium, as well as the incorporation of stakeholder and technical accessibility dimensions as the main components of governance evaluation. The resulting model is expected to serve as a more systematic, adaptive, and relevant instrument for assessing the quality of cooperative governance, while simultaneously supporting greater transparency, accountability, and public trust. Nevertheless, this study still has limitations regarding the number of informants and the absence of extensive empirical testing; therefore, future research is recommended to examine the validity and implementation of the model across various cooperative contexts in Indonesia.